Neurological manifestations by sex and age group in COVID-19 inhospital patients - Pereira, Daniella Nunes; Bicalho, Maria Aparecida Camargos; Jorge, Alzira de Oliveira; Gomes, Angélica Gomides dos Reis; Schwarzbold, Alexandre Vargas; Araújo, Anna Luiza Homan; Cimini, Christiane Corrêa Rodrigues; Ponce, Daniela [UNESP]; Rios, Danyelle Romana Alves; Grizende, Genna Maira Santos; Manenti, Euler Roberto Fernandes; Anschau, Fernando; et al. (Elsevier, 2022)
Introduction: Neurological manifestations have been associated with a poorer prognosis in COVID-19. However, data regarding their incidence according to sex and age groups is still lacking. Methods: This retrospective multicentric cohort collected data from 39 Brazilian hospitals from 17 cities, from adult COVID-19 admitted from March 2020 to January 2022. Neurological manifestations presented at hospital admission were assessed according to incidence by sex and age group. Results: From 13,603 COVID-19 patients, median age was 60 years old and 53.0% were men. Women were more likely to present with headaches (22.4% vs. 17.7%, p < 0.001; OR 1.36, 95% confidence interval [CI] 1.22–1.52) than men and also presented a lower risk of having seizures (OR 0.43, 95% CI 0.20–0.94). Although delirium was more frequent in women (6.6% vs. 5.7%, p = 0.020), sex was not associated with delirium in the multivariable logistc regresssion analysis. Delirium, syncope and coma increased with age (1.5% [18–39 years] vs. 22.4% [80 years or over], p < 0.001, OR 1.07, 95% CI 1.06–1.07; 0.7% vs. 1.7%, p = 0.002, OR 1.01, 95% CI 1.00–1.02; 0.2% vs. 1.3% p < 0.001, OR 1.04, 95% CI 1.02–1.06), while, headache (26.5% vs. 7.1%, OR 0.98, 95% CI 0.98–0.99), anosmia (11.4% vs. 3.3%, OR 0.99, 95% CI] 0.98–0.99 and ageusia (13.1% vs. 3.5%, OR 0.99, CI 0.98–0.99) decreased (p < 0.001 for all). Conclusion: Older COVID-19 patients were more likely to present delirium, syncope and coma, while the incidence of anosmia, ageusia and headaches decreased with age. Women were more likely to present headache, and less likely to present seizures.
Keywords: Age; COVID-19; Delirium; Neurological manifestations; Sex